Desarrollo de un sistema de automatización para una inyectora de plástico MIR 65 en la empresa Insoplastic - Aguirre Paredes, Cristina Vanesa (2018)
The project consisted of the development of an automation system for a MIR 65 plastic injection molding machine, belonging to the Company Insoplastic with the purpose of achieving that the aforementioned injector is controlled by a PLC, thus being able to add new control processes depending on the production. This process allowed eliminating the excessive existing wiring by using mechanical contactors and timers for their operation and that being replaced by a PLC and HMI interface facilitated the interaction between the process and the operator by obtaining a graphical interface of easy interpretation and according to the needs of each product in manufacturing. The automation of the MIR65 provided advantages and economic and social benefits because it ensured a better quality of work performed by the operator in the new system implemented. The reductions of the information processing times are less than those obtained in a manual control by eliminating the chain logic of contactors. With the automation process, a reliable system is guaranteed which can make appropriate decisions to speed up the production process or decide on a failure in said process, with the necessary assurances for the correct operation of the machine and operator protection.